Urbanization, land use transformation and spatio-environmental impacts: Analyses of trends and implications in major metropolitan regions of Ghana. (July 2020) - Asabere, Stephen Boahen; Acheampong, Ransford A.; Ashiagbor, George; Beckers, Sandra Carola; Keck, Markus; Erasmi, Stefan; Schanze, Jochen; Sauer, Daniela
Graphical abstract: Highlights: Paper examines and quantifies the evolution and impact of urbanization in two metropolitan regions of Ghana. Built-up land has increased significantly in the last three decades at the expense of environmental land-cover classes. Urban-open-space land, being in a permanent state of flux, mediates transitions between built-up land and vegetation and vice versa. The emergent landscapes show intensive fragmentation, especially in the suburban and peri-urban zones. Integrative solutions are needed to manage urban growth, avert biodiversity loss and preserve eco-system service supply. Abstract: Urbanization induces spatial and environmental changes. Monitoring and understanding the nature of these changes is crucial to achieving sustainable urban development imperatives. To this end, this paper examines the evolution and spatio-environmental impacts of rapid urbanization in two major metropolitan regions of Ghana—Accra-City Region and the Greater Kumasi Sub-Region. The analysis uses Landsat satellite data and landscape metrics to examine land use transitions and to characterize the emergent landscapes over the last three decades. The results show that built-up land has increased significantly in these metropolitan regions largely at the expense of environmental land cover classes. The expansion process follows a general trend where the historical-core zones were initially sites of rapid land cover conversion to built-up, with settlements in the suburban and peripheral zones expanding in recent years and becoming integrated into the conterminous urban areas of the metropolitan regions. The analysis also uncovered a unique, dynamic and complex process whereby the urban-open-space class, being in a permanent state of flux, mediates transitions between built-up land and vegetation and vice versa. The metric-based land use transformation analysis shows that the landscape of the metropolitan regions has fragmented because of an increased expansion and aggregation of patches of built-up land in the core areas and leapfrog, sprawling expansion in the outlying suburban and peripheral zones. The paper concludes on the need for integrative urban growth management strategies that brings together spatial planning and environmental resource governance to avert the negative consequences on the natural environment of unfettered urban expansion.